Path to the Pacific : the story of Sacagawea - Frazier, Neta Lohnes, 1890-; Frazier, Neta Lohnes, 1890- (New York : Sterling, 2007)
A biography of Sacagawea who accompanied and aided the Lewis and Clark Expedition.
"A Flying Point Press book"--T.p. verso.
Updated ed. of: Sacagawea : the girl nobody knows. D. McKay, 1967.
Maps on endpapers.
Includes bibliographical references (p. 169-170) and index.
Keywords: Sacagawea -- Juvenile literature; Sacagawea; Shoshoni women -- Biography -- Juvenile literature; Shoshoni Indians -- Biography -- Juvenile literature; Women -- Biography; Shoshoni Indians -- Biography; West (U.S.) -- Discovery and exploration -- Juvenile literature; West (U.S.) -- Discovery and exploration